Self-Esteem as a Factor of Economic Identity in Early Adolescence (Empirical Perspective) - Lazarenko, O. (Psychological Prospects Journal, 2013)
The article presents an empirical analysis of the impact of self-identity on the psychological peculiarities of formation of economic identity in early adolescence.
Keywords: economic identity, self-esteem, early adolescence, identity crisis.